A Knowledge, Attitude, and Perception Study on Flu and COVID-19 Vaccination during the COVID-19 Pandemic: Multicentric Italian Survey Insights - Cristina Genovese; Claudio Costantino; Anna Odone; Giuseppe Trimarchi; Vincenza La Fauci; Francesco Mazzitelli; Smeralda D’Amato; Raffaele Squeri; the COVID-19 Risk Perception Group (Vaccines, 2022)
In January 2020, Chinese health authorities identified a novel coronavirus strain never before isolated in humans. It quickly spread across the world, and was eventually declared a pandemic, leading to about 310 million confirmed cases and to 5,497,113 deaths (data as of 11 January 2022). Influenza viruses affect millions of people during cold seasons, with high impacts, in terms of mortality and morbidity. Patients with comorbidities are at a higher risk of acquiring severe problems due to COVID-19 and the flu—infections that could impact their underlying clinical conditions. In the present study, knowledge, attitudes, and opinions of the general population regarding COVID-19 and influenza immunization were evaluated. A multicenter, web-based, cross-sectional study was conducted between 10 February and 12 July 2020, during the first wave of SARS-CoV-2 infections among the general population in Italy. A sample of 4116 questionnaires was collected at the end of the study period. Overall, 17.5% of respondents stated that it was unlikely that they would accept a future COVID-19 vaccine (n = 720). Reasons behind vaccine refusal/indecision were mainly a lack of trust in the vaccine (41.1%), the fear of side effects (23.4%), or a lack of perception of susceptibility to the disease (17.1%). More than 50% (53.8%; n = 2214) of the sample participants were willing to receive flu vaccinations in the forthcoming vaccination campaign, but only 28.2% of cases had received it at least once in the previous five seasons. A higher knowledge score about SARS-CoV-2/COVID-19 and at least one flu vaccination during previous influenza seasons were significantly associated with the intention to be vaccinated against COVID-19 and influenza. The continuous study of factors, determining vaccination acceptance and hesitancy, is fundamental in the current context, in regard to improve vaccination confidence and adherence rates against vaccine preventable diseases.